Analisis Sanitasi pada Food court Baseball UNESA - Jocelyn Handoko; Nugrahani Astuti (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
A Foodcourt Baseball facility held by the surabaya state university (unesa) held in the middle of the ketintang campus. This study aims to determine 1) the location of the building, 2) analysis of sanitation facilities and 3) kitchen sanitation analysis and Baseball Foodcourt dining room. The study was a descriptive qualitative study aimed at illustrating the sanitation conditions at the foodcourt Baseball of surabaya state university, at the ketintang campus in September 2023. The population in this study is the entire stan in the Foodcourt Baseball is by 30 stan. Data recording This research uses the observation method accompanied by documentation and the collecting instrument of the data is the observation sheet. The results of the study show that location of buildings, sanitation facilities, kitchens and foodcourt baseball dining room had not fully qualified according to the decision of the Indonesian ministry of health no. 1098/ menkes/sk/vii /2003. With the study, the surabaya state university business administration, traders' and baseball court sanitation companies are expected to improve the application of sanitation and renew inadequate sanitation facilities.